Biomimetic Nucleic Acid Drug Delivery Systems for Relieving Tumor Immunosuppressive Microenvironment - Wenlu Yan; Ying Cao; Qi Yin; Yaping Li (MDPI AG, 2024)
Immunotherapy combats tumors by enhancing the body's immune surveillance and clearance of tumor cells. Various nucleic acid drugs can be used in immunotherapy, such as DNA expressing cytokines, mRNA tumor vaccines, small interfering RNAs (siRNA) knocking down immunosuppressive molecules, and oligonucleotides that can be used as immune adjuvants. Nucleic acid drugs, which are prone to nuclease degradation in the circulation and find it difficult to enter the target cells, typically necessitate developing appropriate vectors for effective in vivo delivery. Biomimetic drug delivery systems, derived from viruses, bacteria, and cells, can protect the cargos from degradation and clearance, and deliver them to the target cells to ensure safety. Moreover, they can activate the immune system through their endogenous activities and active components, thereby improving the efficacy of antitumor immunotherapeutic nucleic acid drugs. In this review, biomimetic nucleic acid delivery systems for relieving a tumor immunosuppressive microenvironment are introduced. Their immune activation mechanisms, including upregulating the proinflammatory cytokines, serving as tumor vaccines, inhibiting immune checkpoints, and modulating intratumoral immune cells, are elaborated. The advantages and disadvantages, as well as possible directions for their clinical translation, are summarized at last.